Towards a world report on culture and development: Constructing cultural statistics and indicators. Report of the workshop on cultural indicators of development Royaumont foundation, France, 4-7 January 1996 - United Nations Research Institute for Social Development (UNRISD) (United Nations Research Institute for Social Development (UNRISD), 1997)
The joint UNRISD-UNESCO series of Occasional Papers on Culture and Development is a first step in facilitating and catalyzing an international debate on culture and development based on high-quality research. The present paper inaugurates the series by presenting a summary of discussions at the Royaumont Workshop (France, 4-7 January 1996). Readers will find a wealth of information on the issues brought by members of the advisory group, including what might be measured by cultural indicators, how cultural indicators might be constructed and data constraints overcome, the desirability of aggregating statistical data, and a preliminary list of indicators. Thus the present paper also provides valuable background for future papers in the series.
Keywords: 330